Currency in Circulation as An Index of Business Volumes - Hubbard, Joseph B. (The Review of Economics and Statistics, 1931)
XATITH the revisions made in recent years, a most comprehensive body of statistics relating to currency in circulation has been built up, and placed upon a homogeneous basis for an extended period.' This article presents monthly and weekly series for the volume of currency after correction for seasonal variation, and examines such figures in relation to the business and other factors affecting them. Seasonal variation, which forms a large part of the total movement of the weekly and monthly series, was discussed by Mr. Bertrand Fox in this REVIEW, Vol. XIII, pages 26-30, where the weekly indexes of seasonal variation are presented. Monthly seasonal indexes appear on a later page. Business needs for currency determine the seasonal fluctuations of money in circulation, and are the most important cause of other-thanseasonal fluctuations. But influences not of a business nature also affect the series; and explanation for certain of the movements observed in post-war years hinges upon the method used in counting the amount of currency outstanding. The figures apply to money outside (a) the Treasury and (b) the federal reserve banks. The count thus obtained does not embrace the reserve funds of the general banking system, but it does include the till money of banks other than the reserve banks.2 Such till money accounts for something less than one-fifth of the total; the rest is made up of pocket money, merchants' till money, and hoards. Probably bank holdings are to be regarded as an intermediate step through which currency Dasses from the reserve banks into business channels or back from business into the reserve banks. Nevertheless, differences in fluctuations of vault cash and other money have at times been marked. A final point to be noted is that some of the money counted is in circulation outside the United States in Cuba and Canada, for instance, as well as in European countries which absorbed United States currency during and after the war.